Information Systems in Operations Management - Tyrańska, Małgorzata; Walczak, Maciej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Information systems and information technology are an important determinant of revolutionary changes and significantly speed up the development of operations management. The purpose of this article is to present chosen information systems used in operations management. In particular, the paper presents the essence and a model of operations management, and defines the scope of operational decisions. This is followed by an attempt to determine the place and role of information systems and information technology in the evolution of operations management. The final part of the paper focuses on presenting the main features of selected information systems supporting operations management.